Morphometric analysis, multitemporal geomorphological investigation and numerical modelling of the Montebello Sul Sagro large landslide (Abruzzo - Central Italy) - Sciarra, Nicola; Calista, Monia; Miccadei, Enrico; Pasculli, Antonio; Piacentini, Tommaso; Sciarra, Marco (Italian journal of engineering geology and environment, 2017)
<span data-sheets-value=""1":2,"2":"In this work the results of an integrated geomorphological analysis of a complex landslide in Montebello sul Sangro (Abruzzo, Central Italy) are reported. The study is based on a new morphometric analysis of the drainage network, a multi-temporal geomorphological investigation and a numerical landslide modelling. The multi-temporal geomorphological analysis based on the interpretation of aerial photos, LiDAR data and field geomorphological mapping, allowed outlining the recent geomorphological history and multiple activation phases of the landslides. A preliminary analysis of rainfall data showed that the most important landslide reactivations occurred after at least two years with rainfall above average. Some numerical analyses were performed to reconstruct the behaviour on the two main typologies of phenomena affecting the area. Firstly a 2D Finite Difference Method (FLAC, 7.0) was applied to analyse the large landslide affecting the village of Montebello sul Sangro with the aim to study the evolution of the active current landslide and specifically the possible retreat of the main scarp. Then we used the Universal Distinct Element Code (UDEC, 6.0), a two-dimensional numerical software that simulates the quasi-static or dynamic response to loading of media containing multiple and intersecting joint structures, to study the behaviour of the rock mass on which the old village of Buonanotte stands. In order to reconstruct the topography of the Montebello area before the landslide and, accordingly, to explore by computer codes the possible triggering causes of the instability phenomena, autocorrelation of local slope was introduced as a morphometric index of each area of the drainage network. The comparison between the index emerging from the selected landslide area and the other network drainage areas was then exploited."" data-sheets-userformat=""2":13057,"3":"1":0,"11":0,"12":0,"15":"Arial","16":10">In this work the results of an integrated geomorphological analysis of a complex landslide in Montebello sul Sangro (Abruzzo, Central Italy) are reported. The study is based on a new morphometric analysis of the drainage network, a multi-temporal geomorphological investigation and a numerical landslide modelling. The multi-temporal geomorphological analysis based on the interpretation of aerial photos, LiDAR data and field geomorphological mapping, allowed outlining the recent geomorphological history and multiple activation phases of the landslides. A preliminary analysis of rainfall data showed that the most important landslide reactivations occurred after at least two years with rainfall above average. Some numerical analyses were performed to reconstruct the behaviour on the two main typologies of phenomena affecting the area. Firstly a 2D Finite Difference Method (FLAC, 7.0) was applied to analyse the large landslide affecting the village of Montebello sul Sangro with the aim to study the evolution of the active current landslide and specifically the possible retreat of the main scarp. Then we used the Universal Distinct Element Code (UDEC, 6.0), a two-dimensional numerical software that simulates the quasi-static or dynamic response to loading of media containing multiple and intersecting joint structures, to study the behaviour of the rock mass on which the old village of Buonanotte stands. In order to reconstruct the topography of the Montebello area before the landslide and, accordingly, to explore by computer codes the possible triggering causes of the instability phenomena, autocorrelation of local slope was introduced as a morphometric index of each area of the drainage network. The comparison between the index emerging from the selected landslide area and the other network drainage areas was then exploited.